PEMBELAJARAN PENGENALAN HURUF, ANGKA DAN GAMBAR BERWARNA BERBASIS MULTIMEDIA (STUDI KASUS: TK PGRI GODONG) - Syifa Ashafatun; Migunani Migunani; Maya Utami Dewi; Khoirur Rozikin; Arsito Ari Kuncoro (LPPM Politeknik Pratama Kendal, 2025)
This study aims to develop an interactive multimedia-based learning application designed to introduce letters, numbers, and colorful images to early childhood learners. The development model employed is the ADDIE model, which consists of five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. The analysis phase began with identifying field needs, followed by the design of learning media, development of a desktop-based application using Eclipse IDE and the Java programming language, and database integration using MySQL. The trial was conducted at TK PGRI Godong, involving 30 students as research subjects. Evaluation results indicate that the application has a positive impact on students’ understanding, with an overall average score of 93.3%. Validation by content experts (kindergarten teachers) yielded a feasibility score of 92%, while media experts gave a score of 88%. Classroom observations showed that students were more enthusiastic, focused, and better able to understand the material compared to conventional methods. Based on these findings, the learning application is deemed highly feasible and effective as a supporting medium in early childhood education.